Great Britain and the Nova Scotian Confederate and Repeal movements, 1864–9. Issue 2 (September 2018) - Rodorff, Mathias
Abstract : This article discusses how the desire to maintain the connection to the 'mother country' contributed to the outcome of the movements for and against Confederation in Nova Scotia. In the 1860s, no opinion polls were conducted, but newspapers were the major arena of distributing news and expressing views. They offer an important insight into the opinions of Nova Scotians towards Confederation during the critical time when they bitterly debated about remaining or leaving the Dominion of Canada. Moreover, they illustrate views about the risk of breaking their affiliation with the 'mother country'in order to achieve the repeal of their admission into the Dominion of Canada.